2007
DOI: 10.1002/anie.200700021
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of β‐Ketoesters by Ruthenium(II)–Binap‐Catalyzed Asymmetric Hydrogenation

Abstract: Please, after you…︁ β‐Ketoesters in mixtures underwent Noyori reduction one by one at room temperature under 4 bar of hydrogen pressure in the presence of a catalyst formed from RuII and (S)‐binap (see example). The rate of the asymmetric hydrogenation and hence the selectivity for a particular β‐ketoester was found to depend on the Lewis basicity of the ester group. Binap=2,2′‐bis(diphenylphosphanyl)‐1,1′‐binaphthyl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…This justifies the assumption that the two remaining Weinreb amides shown in Table have analogous 3D structures. This would mean that the rule “hydrogenations catalyzed by Ru complexes of S ‐BINAP establish dashed C–OH bonds – provided the product is drawn with the orientation shown for 2 –” applies not only to such hydrogenations of β‐keto esters and β‐keto amides,[7b] but to β‐keto Weinreb amides as well.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This justifies the assumption that the two remaining Weinreb amides shown in Table have analogous 3D structures. This would mean that the rule “hydrogenations catalyzed by Ru complexes of S ‐BINAP establish dashed C–OH bonds – provided the product is drawn with the orientation shown for 2 –” applies not only to such hydrogenations of β‐keto esters and β‐keto amides,[7b] but to β‐keto Weinreb amides as well.…”
Section: Resultsmentioning
confidence: 99%
“…This pioneering reaction did not attract many followers until we reported that an H 2 pressure of 5 bar is sufficient for Ru‐catalyzed asymmetric hydrogenations of β‐keto amides to go to completion at room temp. within less than 1 d . These conditions are generalizable:, by using the dinuclear Ru II complex [Et 2 NH 2 ] + {[RuCl( S )‐BINAP] 2 (µ‐Cl) 3 } – (0.5 mol‐%), with ethanol as the solvent, a hydrogen pressure of 4 bar, and reaction times of 14–36 h, β‐hydroxy amides become available with over 91 % ee .…”
Section: Introductionmentioning
confidence: 99%
“…A Reformatsky-type reaction of 18 mediated by SmI 2 , followed by oxidation of the resulting hydroxy ester, afforded the corresponding bketoester 20. Gratifyingly, catalytic asymmetric hydrogenation of 20 with 1 mol % [23] afforded 21 in 90 % yield, with an excellent de value of > 99 %. Protection of 21 with TBSOTf, followed by basic hydrolysis resulted in A.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, only limited examples were reported with these difficult substrates 10,48. The amide moiety tended to have a stronger coordination ability than esters,49 so we speculated that γ‐keto amides might be easier to hydrogenate. In the presence of CeCl 3 •7H 2 O as the additive, N , N ‐dimethyl‐4‐oxo‐4‐phenylbutanamide ( 34a ) was hydrogenated to give 35a in 85% ee (Scheme ) 50.…”
Section: γ‐ and δ‐Functionalized Ketones And Simple Ketonesmentioning
confidence: 97%